A national survey of inpatient medication systems in English NHS hospitals - McLeod, Monsey (BioMed Central, 2014)
BACKGROUND: Systems and processes for prescribing, supplying and administering inpatient medications can have substantial impact on medication administration errors (MAEs). However, little is known about the medication systems and processes currently used within the English National Health Service (NHS). This presents a challenge for developing NHS-wide interventions to increase medication safety. We therefore conducted a cross-sectional postal census of medication systems and processes in English NHS hospitals to address this knowledge gap. METHODS: The chief pharmacist at each of all 165 acute NHS trusts was invited to complete a questionnaire for medical and surgical wards in their main hospital (July 2011). We report here the findings relating to medication systems and processes, based on 18 closed questions plus one open question about local medication safety initiatives. Non-respondents were posted another questionnaire (August 2011), and then emailed (October 2011). RESULTS: One hundred (61% of NHS trusts) questionnaires were returned. Most hospitals used paper-based prescribing on the majority of medical and surgical inpatient wards (87% of hospitals), patient bedside medication lockers (92%), patients’ own drugs (89%) and ‘one-stop dispensing’ medication labelled with administration instructions for use at discharge as well as during the inpatient stay (85%). Less prevalent were the use of ward pharmacy technicians (62% of hospitals) or pharmacists (58%) to order medications on the majority of wards. Only 65% of hospitals used drug trolleys; 50% used patient-specific inpatient supplies on the majority of wards. Only one hospital had a pharmacy open 24 hours, but all had access to an on-call pharmacist. None reported use of unit-dose dispensing; 7% used an electronic drug cabinet in some ward areas. Overall, 85% of hospitals had a double-checking policy for intravenous medication and 58% for other specified drugs. “Do not disturb” tabards/overalls were routinely used during nurses’ drug rounds on at least one ward in 59% of hospitals. CONCLUSIONS: Inter- and intra-hospital variations in medication systems and processes exist, even within the English NHS; future research should focus on investigating their potential effects on nurses’ workflow and MAEs, and developing NHS-wide interventions to reduce MAEs.